Influence of Organizational Commitment and Financial Compensation on the Production Employees’ Performance at PT Fumira Semarang - Meita - Salsabilasari; M - Nahar; Dody - Setyadi (Politeknik Negeri Semarang, 2022)
This study aims to examine respondent’s perceptions of organizational commitment and financial compensation on the production employees’ performance at PT Fumira Semarang. This study uses a quantitative approach and uses a sample of 42 employees. The data collection method used in this research are questionnaire, interview, and literature review. While the analysis technique is multiple linear regression analysis which is equipped with classical assumption test, test t, test F, and coefficient of determination using SPSS 25 software. The regression equation is Y = 2,955 + 0,222X1 + 0,428X2.. The coefficient of determination (R2) is 36,2%. The results of this study indicate that organizational commitment (X1) and financial compensation (X2) has a significant effect on employee performance (Y). The results show that organizational and financial compensation simultaneously influenced employee performance